Bacterial pneumonia in children: Risk factors, symptoms, treatments and diagnoses - Lima, Lucas Alves de Oliveira; Lessa, Mikhael Buzon; Luz, Tássio Rômulo Silva Araújo; Alves, Francisco Eduardo Ferreira; Pinheiro, Isabela Malerba; Neto, Manoel Pereira da Silva; Silva, Erlândia Maria da; Andrade, Jennyfer Souza; Monteiro, Danniele Chagas (Seven Editora, 2024)
The present research aimed to analyze the main risk factors associated with bacterial pneumonia in children, the most common symptoms presented by pediatric patients affected by this infection, as well as the main methods used for the diagnosis and treatment of this condition. To achieve this, a bibliographic research was conducted, and as a result, it was found that bacterial pneumonia in children can be severe if not properly treated. Risk factors such as age, lack of immunization, unfavorable socioeconomic conditions, and exposure to passive smoking are associated with this condition. The diagnosis of such an illness involves clinical evaluation and complementary tests, such as chest radiography. Treatment, on the other hand, includes the use of prescribed antibiotics, rest, and adequate hydration. DOI:https://doi.org/10.56238/sevened2024.001-053